Museu Parque Seringal: proposta no ensino de História e natureza - CONCEIÇÃO, Ana Maria da Silva (Universidade Federal do Pará, 2023)
The present work makes a study about the heritage set of the Museu Parque Seringal, in Ananindeua/PA, as a space that collaborates for the teaching and learning process, in order to contextualize the relationship between past and present of the history of the municipality for the const ruction of historical knowledge that considers nature as a source of learning for the discipline of History. Here we present the results of a field work that involved elementary school students from the “Cândido Horácio Evelin” Middle School. The objective is to launch new perspectives on the park in order to rethink how that place contributes to the teaching of History, using the narratives and knowledge produced by the 9th grade students and also the previous knowledge of the community around the park. It was intended to demonstrate that museums are living spaces and places of memory that dialogue with our present and that keep their specificities and that, therefore, must be preserved within an interdisciplinary perspective that implies the relationships between memory, history and nature contained in the space that shelters rubber trees ( Hevea brasiliensis ). The educational product associated with this research is a folder that will help future guided visits to the Museum. The folder has guidelines, a pho to gallery, hyperlinks and QR Code that make the experience more interactive and immersive and can be used by teachers, students and the general public.